Constraints on accretion disk size in the massive type 1 quasar PG 2308+098 from optical continuum reverberation lags. (19th September 2018) - Kokubo, Mitsuru
Abstract: Two years' worth of u-, g-, r-, i -, and z -band optical light curves were obtained for the massive type 1 quasar PG 2308+098 at z = 0.433 using the 1.05 m Kiso Schmidt telescope/Kiso Wide Field Camera, and inter-band time lags of the light curves were measured. Wavelength-dependent continuum reverberation lag signals of several tens of days relative to the u -band were detected at g, r, i, and z bands, where the longer wavelength bands showed larger lags. From the wavelength-dependent lags, and assuming the standard disk temperature radial profile $T \propto R_{\rm disk}^{-3/4}$ and an X-ray/far-ultraviolet reprocessing picture, a constraint on the radius of the accretion disk responsible for the rest-frame 2500 Å disk continuum emission was derived as $R_{\rm disk} = 9.46^{+0.29}_{-3.12}\:$ light-day. The derived disk size is slightly (1.2–1.8 times) larger than the theoretical disk size of R disk = 5.46 light-day predicted from the black hole mass ( M BH ) and Eddington ratio estimates of PG 2308+098. This result is roughly in accordance with previous studies of lower-mass active galactic nuclei (AGNs), where measured disk sizes have been found to be larger than the standard disk model predictions by a factor of ∼3; however, the disk size discrepancy is more modest in PG 2308+098. By compiling literature values of the disk size constraints from continuum reverberation and gravitational microlensing observations for AGNs/quasars, we show that the M BH dependence of R disk is weaker than that expected from the standard disk model. These observations suggest that the standard Shakura–Sunyaev accretion disk theory has limitations in describing AGN/quasar accretion disks.